(untitled) (Praxis Educativa, 2020)
Today’s society requires the education of global citizens who may be able to deal with inequalities and to promote a sustainable society. This study focuses on the development of critical thinking by students through the reflections recorded in their diaries during a teaching experience that addresses issues of social justice such as the inequalities between countries and the exploitation of children. A qualitative approach has been developed to analyze the information collected in the students’ and teacher’s diaries: a series of categories and criteria have been established and the data of the participants have been encoded to guarantee their anonymity. The results evidence that during the experience they have developed a critical judgment, managing to reflect on the importance of living in an egalitarian and fair society. In conclusion, the experience shows that it is possible to address social justice in the classroom with satisfactory results. Keywords: social justice; critical thinking; primary education; global citizenship